Primary adult choroid plexus carcinomas: a single-center experience with a systematic review - Zuo, Pengcheng; Mai, Yiying; Jiang, Zhuang; Zhang, Bochao; Wang, Yujin; Zhang, Mingxin; Wu, Zhen; Zhang, Junting; Zhang, Liwei (Frontiers in Oncology, 2023)
Objective Primary adult choroid plexus carcinomas (PACPCs) are extremely rare brain tumors. The existing literature primarily comprises case reports, which limits our understanding of this uncommon disease. This study aims to describe the clinical characteristics and prognosis of PACPCs, as well as to identify optimal treatment strategies. Methods We conducted a comprehensive analysis of clinical data from 7 patients with PACPCs who underwent surgical treatment at the Department of Neurosurgery, Beijing Tiantan Hospital, between March 2011 and March 2023. Additionally, a thorough search of the PubMed database was performed using the keywords “choroid plexus carcinoma” or “choroid plexus carcinomas” within the time frame of August 1975 to April 2023, which yielded a total of 28 identified cases. Subsequently, we evaluated risk factors for progression-free survival (PFS) and overall survival (OS) based on the pooled cases. Results The pooled cohort, consisting of 7 cases from our institution and 28 cases from the literature, included 20 males and 15 females with a mean age of 44.3 ± 14.7 years (range: 21-73 years). Gross-total resection (GTR) and non-GTR were achieved in 22 (62.9%) and 13 (37.1%) patients, respectively. Radiotherapy and chemotherapy were administered to 29 (90.6%) and 13 (40.6%) patients, respectively. After a mean follow-up of 21.0 ± 26.7 months (range: 2-132 months), 18 patients were alive, and 11 patients had died. The multivariate Cox regression model demonstrated that non-GTR (HR 5.262, 95% CI 1.350-20.516, p=0.017) was a negative prognostic factor for OS. However, we did not find any risk factors for PFS. Conclusion Complete surgical resection should be considered as the primary treatment approach for this rare disease. Chemotherapy and radiotherapy appear to have limited effectiveness in treating this condition. Further research with large cohorts is needed to validate our conclusions.